Relasi Ilmu, Filsafat dan Agama Dalam Dimensi Filsafat Ilmu - Abu Tamrin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2019)
Abstract:Philosophy is one of the fields of science that examines how to think deeply about something. Understanding of science comes from the Arabic words ‘science, English science, Dutch watenchap, and German wissenchap. Knowledge can be a science if it has special characteristics, arranged methodically, systematically, electronically (related) about a particular field and reality. Classification of science classification has developed according to its era. There are 5 truth theories according to Williams. Besides that there are positivistic, essentialistic, constructivist, and requistic theories. One field of philosophy is epistimologi often called the theory of knowledge. There are two theories of knowledge, namely realism and idealism. The method of gaining knowledge: empiricism, rationalism, phenomenalogical teachings of Khan. Methods in the theory of knowledge: Inductive, contemplative and dialectical. The next paper discusses religion which is an Indonesian term. Religion (English), religion (Dutch), and din (Arabic). There is a word between religion and life. In Islam there is a religion of heaven (samawi) or "religion of revelation" and there is "religion of the earth" (ardhi) or "religion of non-revelation". According to Max Weber, there is no society without religion. Science, philosophy, and religion have their respective functions and have differences and coherence.Keywords: Science, Philosophy, Religion, Comparison. Abstrak: Filsafat merupakan salah satu bidang  ilmu yang mengkaji cara berpikir secara mendalam tentang sesuatu. Pengertian ilmu berasal dari kata bahasa Arab ‘ilmu, Inggris science, Belanda watenchap, dan Jerman wissenchap. Pengetahuan dapat menjadi ilmu apabila mempunyai karakteristik khusus, disusun secara metodis, sistematis, kohern (bertalian) tentang suatu bidang tertentu dan kenyataan (realitas). Klasifikasi penggolongan ilmu mengalami perkembangan sesuai zamannya. Ada 5 teori kebenaran menurut Williams. Selain itu ada teori positivistik, esensialistik, konstruktivitik, dan requistik. Salah satu bidang filsafat adalah epistimologi sering disebut teori pengetahuan (theory of knowledge). Ada dua teori pengetahuan, yaitu realisme dan idealisme. Metode memperoleh pengetahuan: empirisme, rasionalisme, fenomenalogis ajaran Khan. Metode dalam teori pengetahuan: Induktif, kontemplatif, dan dialektis. Makalah selanjutnya membahas agama yang merupakan istilah Indonesia. Religion (bahasa Inggris), religi (bahasa Belanda), dan din (bahasa Arab). Ada kata antara agama dengan kehidupan. Dalam agama Islam ada agama langit (samawi) atau “agama wahyu” dan ada “agama bumi” (ardhi) atau “agama non wahyu”. Menurut Max Weber, tidak ada masyarakat tanpa agama. Ilmu, filsafat, dan agama punya fungsi masing-masing dan mempunyai perbedaan dan pesamaan.Kata kunci: Ilmu, Filsafat, Agama, Perbandingan.